THE EFFECTIVENESS OF THE WEBSITE AS AN INTERACTIVE MEDIUM IN INFORMATION SERVICES (STUDY OF THE EFFECTIVENESS OF THE SOLOK CITY GOVERNMENT WEBSITE) - Arianto, Arianto; Arif, Ernita; Asmawi , Asmawi (INFOKUM, 2022)
This study aims to measure how effective the website is as an interactive media in providing information to the people of Solok City. The focus of this research is to analyze and describe the level of effectiveness of website use by the public and find out the relationship between characteristics and the level of effectiveness of website users using DeLone & McLean theory (D&M IS Success Model). The methodology used in this study is an explanatory quantitative approach with a survey method. The research in collecting data is to use a closed questionnaire using Google From. In this study, there were 96 respondents who would later be analyzed with correlations with SPSS IBM SPSS Statistics 26. From the results of the spearman rank correlation test, a negative relationship was obtained with an age of (-0.104). From the results of the chi-square test, it was found that there was no significant relationship between gender and the effectiveness of website use in public services. From the correlation of education level with the effectiveness of website use by (0.037).